Julia L. Frengs. Corporeal Archipelagos: Writing the Body in Francophone Oceanian Women’s Literature. Lexington Books, 2017. - Liana Babayan (Studies in 20th & 21st Century Literature, 2018)
Review of Julia L. Frengs. Corporeal Archipelagos. Writing the Body in Francophone Oceanian Women’s Literature. Lexington Books, 2017. ix + 236 pp.
Keywords: Book Review; Julia L Frengs; Corporeal Archipelagos: Writing the Body in Francophone Oceanian Women’s Literature